Managing Port Reforms in India: Case Study of Jawaharlal Nehru Port Trust (JNPT) Mumbai - Ray, Amit S. (Washington, DC: World Bank, 2012)
JNPT was established with the goal of creating a world-class port and, though it enjoyed an edge over other Indian ports with respect to both infrastructure and performance, inherent drawbacks prevented it from achieving world standards in port efficiency. JNPT was selected as a test case in the privatization of port operations and key reforms undertaken have been reasonably successful. With the creation of a new private terminal and the follow-up measures undertaken thereafter, JNPT has demonstrated its capability to enhance efficiency of the public terminal through the introduction of intra-port competition and it has succeeded in earning the distinction of being the worlds 29th largest container port.